If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(2t + -2) + 8t = 4t + -7 Reorder the terms: -5(-2 + 2t) + 8t = 4t + -7 (-2 * -5 + 2t * -5) + 8t = 4t + -7 (10 + -10t) + 8t = 4t + -7 Combine like terms: -10t + 8t = -2t 10 + -2t = 4t + -7 Reorder the terms: 10 + -2t = -7 + 4t Solving 10 + -2t = -7 + 4t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-4t' to each side of the equation. 10 + -2t + -4t = -7 + 4t + -4t Combine like terms: -2t + -4t = -6t 10 + -6t = -7 + 4t + -4t Combine like terms: 4t + -4t = 0 10 + -6t = -7 + 0 10 + -6t = -7 Add '-10' to each side of the equation. 10 + -10 + -6t = -7 + -10 Combine like terms: 10 + -10 = 0 0 + -6t = -7 + -10 -6t = -7 + -10 Combine like terms: -7 + -10 = -17 -6t = -17 Divide each side by '-6'. t = 2.833333333 Simplifying t = 2.833333333
| 2x^2+14x-20= | | Y=9x-22 | | -x+7=4 | | 6x=10*12 | | -(3x-8)= | | 7(x-1)=(x-5) | | x-0.4x=141 | | 13-x=48 | | 9x+15-8x-4=2 | | (-x+5)+4=5x+5 | | 3(52x+7)=6x | | x+16/40=1/2 | | 57=x+15 | | 5w-8w+3=-8 | | y=-5x^2+60x+30 | | p(x)=-5x^2+60x+30 | | 5x-24=5 | | 3x^2+6x-3= | | -2x-4x=3 | | log[4](3x)=2 | | 5x+38=6x+32 | | 2h+1.4=15-h | | -2x-4=3 | | 7.6+0.9x=0.4 | | 5k-8=7k | | 3.9x-41=2.9x+4 | | (3x-10)+(5x+30)=180 | | A^2+b^2=80*80 | | 8x+8.32=5x+13 | | 3x(x-1)+11=7 | | 11c-8=22-4c | | 3x(x-1)+11=7solve |